Analysis of Takayasu's Arteritis as a Risk Factor for Acute Coronary Syndrome - Maria Emilia Romero Noboa, MD; Shilpa Arora, MD; Preeti Kansal, MD; Augustine M. Manadan, MD (American Journal of Medicine Open)
ABSTRACT: Introduction: Takayasu's arteritis (TAK) is a rare chronic granulomatous vasculitis that primarily affects the aorta and its major branches but is also known to affect the coronary arteries. This involvement can result in acute coronary syndrome (ACS). This study aims to analyze TAK as an ACS risk factor in a US adult inpatient population. Methods: We performed a retrospective study of ACS in 2016-2020 National Inpatient Sample (NIS) database. TAK and traditional cardiovascular (CV) risk factors were included in a multivariable logistic regression analysis for an outcome of ACS. The results were reported as adjusted odds ratios (ORadj) with P values <.05 considered significant. Results: There were 148,767,786 adult hospitalizations in the 2016-2020 NIS database. Of the 3,282,749 hospitalizations with ACS, 180 (0.005%) had TAK. Multivariable analysis showed that age (ORadj 1.02), lowest income quartile (ORadj 1.03), diabetes (ORadj 1.19), hypertension (ORadj 1.06), hyperlipidemia (ORadj 2.94), nicotine dependence/tobacco use (ORadj 1.96), obesity (ORadj 1.21), and TAK (ORadj 1.78) were associated with a higher odds of ACS. Conclusions: Despite rare occurrence of concurrent ACS and TAK, we found TAK was independently associated with ACS similar to traditional CV risk factors. These results should alert physicians to the high risk of ACS in TAK inpatients.